2023
DOI: 10.3389/fendo.2023.1266692
|View full text |Cite
|
Sign up to set email alerts
|

Alanine aminotransferase to high- density lipoprotein cholesterol ratio is positively correlated with the occurrence of diabetes in the Chinese population: a population-based cohort study

Shiming He,
Changhui Yu,
Maobin Kuang
et al.

Abstract: ObjectiveBoth alanine aminotransferase (ALT) and high-density lipoprotein cholesterol (HDL-C) are closely related to glucose homeostasis in the body, and the main objective of this study was to investigate the association between ALT to HDL-C ratio (ALT/HDL-C ratio) and the risk of diabetes in a Chinese population.MethodsThe current study included 116,251 participants who underwent a healthy physical examination, and the study endpoint was defined as a diagnosis of new-onset diabetes. Multivariate Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…This conclusion was obtained in a multiple regression model and after controlling of confounding variables such as waist circumference, hypertension and sex. To the best of our knowledge, this report is the first study in Iran that measured the association between this ratio and DM, furthermore, it is one of the few reports worldwide investigating this issue, with results similar to two other existing articles 20 , 21 . Our findings indicate that individuals with DM tend to have higher levels of ALT and lower levels of HDL-C. Other studies have also demonstrated that individuals with DM have higher ALT levels compared to those without DM, and that elevated ALT levels are directly linked to the development of DM 11 13 , 24 26 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This conclusion was obtained in a multiple regression model and after controlling of confounding variables such as waist circumference, hypertension and sex. To the best of our knowledge, this report is the first study in Iran that measured the association between this ratio and DM, furthermore, it is one of the few reports worldwide investigating this issue, with results similar to two other existing articles 20 , 21 . Our findings indicate that individuals with DM tend to have higher levels of ALT and lower levels of HDL-C. Other studies have also demonstrated that individuals with DM have higher ALT levels compared to those without DM, and that elevated ALT levels are directly linked to the development of DM 11 13 , 24 26 .…”
Section: Discussionsupporting
confidence: 81%
“…Recently, a longitudinal study with a follow-up period of 3.1 years revealed that the ratio of ALT to HDL was positively associated with the prediction of diabetes. This ratio was found to be superior to considering ALT and HDL-C separately 21 . The ALT to HDL-C ratio has been introduced as a combined marker for early diagnosis of DM.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, an elevation in HDL-C is widely recognized as a protective factor against IR ( 28 ). Furthermore, recent studies have proposed that the combination of HDL-C and ALT may serve as a more sensitive and novel biomarker for assessing inflammatory and metabolic disorders ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cao et al conducted a study investigating the combination of HDL-C and ALT, and the findings suggest that the ALT/HDL-C ratio serves as a valuable novel predictor for the risk in the development of diabetes in Japanese ( 14 ). He et al conducted a study on a total of 116,251 Chinese people and found a positive correlation between the risk in the development of diabetes and the ALT/HDL-C ( 15 ). However, the existence of an association between IR risk and ALT/HDL-C remains unclear.…”
Section: Introductionmentioning
confidence: 99%